Ornate pillar of the Neelkanth Mahadev group of temples - Temples of India Project Team (Jio Institute, 2024)
Seen here is a closer view of the pillar in the central chatuski (slightly elevated platform with four pillars) of the mandapa (pillared hall) of the Neelkanth Mahadev Temple. This pillar typology is similar to the pillars of the mukhamandapa (front porch). Octagonal shafts with foliage ornamentation, maladharas (garland bearers), and sculptures on all sides of the shafts are characteristics of the pillar. This is one of the most ornate varieties of pillars in all of the Neelkanth Mahadev group of temples.